2017
DOI: 10.1155/2017/9764843
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Uric Acid‐Lowering Effects of the Combination of Chrysanthemum indicum Linne Flower and Cinnamomum cassia (L.) J. Persl Bark Extracts

Abstract: Chrysanthemum indicum Linne flower (CF) and Cinnamomum cassia (L.) J. Persl bark (CB) extracts have served as the main ingredients in several prescriptions designed to treat hyperuricemia and gout in traditional Chinese and Korean medicine. However, little is known about the combination effects of a CF and CB (CC) mixture on hyperuricemia. In our study, we investigated the antihyperuricemic effects of CC mixture and the mechanisms underlying these effects in normal and potassium oxonate- (PO-) induced hyperuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…Based on our previous research, we further study the understanding of the mechanism underlying the antihyperuricemic effects. In this study, we found that DKB114 significantly decreased serum uric acid levels in normal rats and rats with PO-induced hyperuricemia, consistent with that of our previous study and other studies [ 18 , 19 , 20 , 21 ]. Furthermore, DKB114 increased uric acid levels in urine, indicating that DKB114 has the ability to increase uric acid excretion and that it might be a potent uricosuric agent, which may explain its antihyperuricemic effects.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Based on our previous research, we further study the understanding of the mechanism underlying the antihyperuricemic effects. In this study, we found that DKB114 significantly decreased serum uric acid levels in normal rats and rats with PO-induced hyperuricemia, consistent with that of our previous study and other studies [ 18 , 19 , 20 , 21 ]. Furthermore, DKB114 increased uric acid levels in urine, indicating that DKB114 has the ability to increase uric acid excretion and that it might be a potent uricosuric agent, which may explain its antihyperuricemic effects.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, inhibition of XOD activity should be a target to control hyperuricemia. In our study, DKB114 inhibited the in vitro XOD and hepatic XOD activity in rats with PO-induced hyperuricemia, which supports the findings of previous studies [ 18 , 19 , 20 , 21 ]. Furthermore, DKB114 decreased liver uric levels in hyperuricemic models, indicating that inhibition of XOD activity by DKB114 might be attributable to the reduction in uric acid production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, it significantly improves oxidative stress in renal tissues by suppression of free radical generation and potentiation of ADS elements [60]. Also, oral administration of cinnamaldehyde decreases serum uric acid levels and that can be explained by its ability to inhibit the activity of xanthine oxidase enzyme [33].…”
Section: Discussionmentioning
confidence: 99%